A novel open CNC architecture based on STEP-NC data model and IEC 61499 function blocks - Minhat, Mohamad; Vyatkin, Valeriy; Xu, Xun; Wong, Soon; Al-Bayaa, Zina (www.elsevier.com, 2009)
Modern manufacturing industries demand computer numeric controllers, having higher level input languages than outdated G-code, and less proprietary vendor dependencies. IEC 61499 is a new standard for distributed measurement and control systems, that enables portability and interoperability of embedded controllers, along with the ease of their mapping to arbitrary distributed networking hardware configurations. This paper demonstrates that the IEC 61499 reference architecture can be successfully used to create a computer numeric controller, offering interoperability, portability, configurability, and distribution characteristics. The layered CNC-FB architecture is proposed, which simplifies the design of a CNC machine controller with the architecture layers responsible for data processing, data storage and execution. In combination with the object-oriented Model-View-Control design pattern, the CNC-FB architecture supports the design framework, in which simulation of the machining becomes natural and inherent part of the design process, with seamless transition from simulation to actual machining. The implemented controller was tested in both the model and on an actual milling machine.